Gypenoside L and Gypenoside LI Inhibit Proliferation in Renal Cell Carcinoma via Regulation of the MAPK and Arachidonic Acid Metabolism Pathways - Liu, Hui; Li, Xiuming; Xie, Jinbo; Lv, Chengcheng; Lian, Fangchao; Zhang, Shouyi; Duan, Yu; Zeng, Yu; Piao, Xianglan (Frontiers in Pharmacology, 2022)
Renal cell carcinoma (RCC) has the highest mortality rate of all urological malignancies. Clear cell renal cell carcinoma (ccRCC) accounts for approximately 80% of all RCC cases, and is often accompanied by the accumulation of lipid droplets. Growing evidence indicates that ccRCC is a metabolism-related disease. Gypenosides are commonly used for the clinical treatment of hyperlipidemia, and their anti-tumor activity has also been recognized. However, the potential inhibitory effects and mechanisms of action of gypenoside L (Gyp L) and gypenoside LI (Gyp LI) in ccRCC remain unclear. In this study, we confirmed that Gyp L and Gyp LI significantly inhibited proliferation and induced apoptosis in ccRCC cells in vitro. We performed network pharmacology and RNA-seq, and verified the results by western blotting, RT-qPCR, and immunofluorescence experiments. Our results demonstrated that Gyp L and Gyp LI upregulate the expression of COX2 and downregulate the expression levels of cPLA2 and CYP1A1, resulting in reduced arachidonic acid and apoptosis. Gyp L and Gyp LI upregulated the protein levels of DUSP1, p-JUN, and p-JNK, and downregulated p-MEK1/2, p-ERK, and p-P38 levels. Moreover, gypenosides significantly inhibited tumor growth in vivo, and gypenosides significantly reduced cPLA2 and CYP1A1 expression. Furthermore, we performed absolute quantification of arachidonic acid content in ccRCC cells and tumor tissues by HPLC-MS, and found that the arachidonic acid content was significantly reduced after Gyp L, Gyp LI, and gypenoside intervention. In conclusion, our data suggest that Gyp L, Gyp LI, and gypenosides decrease the content of arachidonic acid in ccRCC cells and tumor tissues, but do not have cytotoxic effects on nude mice. Thus, Gyp L, Gyp LI, and total gypenosides extracted from Gynostemma pentaphyllum exhibited anti-tumor activities against ccRCC.